2014
DOI: 10.1002/jctb.4368
|View full text |Cite
|
Sign up to set email alerts
|

Chemical surface modified‐activated carbon cloth for catalytic wet peroxide oxidation of phenol

Abstract: BACKGROUND: Activated carbons (AC) can be used as catalyst in advanced oxidation processes due to the potential activity for hydrogen peroxide decomposition to hydroxyl radicals. Chemical surface groups and textural properties can play a crucial role in its catalytic behaviour. The pH of the reaction medium can also affect the adsorption properties of AC and the chemistry of hydrogen peroxide in catalytic oxidation processes. The AC/H 2 O 2 systems have been successfully used for the degradation of some organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is clear that the trend of removal percentage changed twice with the increase of modification time and temperature, and the value of removal percentage increased slowly when the % removal touched the bottom. The phenomenon may be caused by the following two factors . (i) During the whole modification process, the [Bmim]OH dissolved the dissociative organic composite which led to microporous expansion, and consequently the MB uptake increased.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that the trend of removal percentage changed twice with the increase of modification time and temperature, and the value of removal percentage increased slowly when the % removal touched the bottom. The phenomenon may be caused by the following two factors . (i) During the whole modification process, the [Bmim]OH dissolved the dissociative organic composite which led to microporous expansion, and consequently the MB uptake increased.…”
Section: Resultsmentioning
confidence: 99%
“…Solid adsorption uses porous media to adsorb pollutants by physical or chemical means, and its treatment efficiency depends on the selection of materials and subsequent waste treatment 20 , 26 . This method is efficient and easy to use, but the price of the adsorbent material affects the feasibility of practical applications 27 , 28 . In this research, Solid adsorption and liquid oxidation are combined effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, acid or alkali chemical treatment of activated carbon is an economic and feasible modification method. 15 Belhamdi et.al produce low cost activated carbons from date stones wastes for the adsorption of L-phenylalanine, The activated carbons were prepared by chemical activation with KOH (ACK) and ZnCl 2 (ACZ), a kinetic, equilibrium and thermodynamic study were reported. 16 And their team also research the adsorption mechanisms of free amino acid L-tryptophan from aqueous solution by biomass-based activated carbon by H 3 PO 4 activation adsorption using activated carbon based on agricultural waste (date stones).…”
Section: Introductionmentioning
confidence: 99%
“…The surface oxygen‐containing functional groups and pore structure of activated carbon can be modified by physical, chemical and electrochemical treatment. Among them, acid or alkali chemical treatment of activated carbon is an economic and feasible modification method 15 . Belhamdi et.al produce low cost activated carbons from date stones wastes for the adsorption of L‐phenylalanine, The activated carbons were prepared by chemical activation with KOH (ACK) and ZnCl 2 (ACZ), a kinetic, equilibrium and thermodynamic study were reported 16 .…”
Section: Introductionmentioning
confidence: 99%